Adaptive Hybrid Overcurrent Protection Scheme with High Shares of Distributed Energy Resources - Gourab Banerjee; Christian Hachmann; Jan Lipphardt; Nils Wiese; Martin Braun (Energies)
In this research paper, an adaptive and intelligent protection scheme is developed that brings selectivity and sensitivity to the conventional overcurrent relays considering the changes in grid topologies, changes in grid operation modes, and changes in short-circuit behavior due to the contributions from distributed energy resources in the medium-voltage distribution grids. A quasi-static medium-voltage benchmark grid model is used in the Python-based power system tool pandapower. Definite-time overcurrent relay devices are extended with a communication signal-based tripping scheme suitable for a decentralized communication architecture. Current phasor angles are compared between two primary relays and the result is fed into a tripping logic to achieve selectivity of the primary protection. Furthermore, communication between the primary and backup relays is established, extending the communication signal-based tripping scheme. It analyzes in which cases the proposed communication-based protection scheme’s ability to isolate the faulty section after short-circuit events is comparable to conventional schemes based on distance relays that require additional voltage measurements or differential relays that require dedicated high-speed communication. Therefore, the pre-existing and installed communication capabilities can be used to avoid the need for additional measurement hardware or communication technology.